Inter-Individual Variability of a High-Intensity Interval Training with Specific Techniques Vs. Repeated Sprints Program in Sport-Related Fitness of Taekwondo Athletes - Herrera-Valenzuela, T (Frontiers Media S.A., 2021)
This study investigated the effect of 4 weeks of high-intensity interval training (HIIT) with specific techniques (TS-G) vs. repeated sprints (RS-G) and analyzed the inter-individual variability [classified into responders (Rs) and non-responders (NRs)] on sport-related fitness in taekwondo (TKD) athletes. Athletes of both genders (n = 12) were randomly assigned into TS-G and RS-G groups. Both groups trained 3 days/week for 4 weeks [two blocks of three rounds of 2 min of activity (4-s of all-out efforts with 28-s dynamical pauses) with 1 min of recovery in between and 5 min between blocks] during their regular training. The related sport fitness assessments included squat jump (SJ), countermovement jump (CMJ), multiple frequency speed of kick test (FSKTMULT), specifically total kicks and Kick Decrement Index (KDI), and 20-m shuttle run (20MSR). Relevant results indicate a significant effect of the time factor in both groups for SJ performance and a significant decrease for KDI in RS-G. In addition, an improvement in performance according to the effect size analysis in the TS-G in total kicks, KDI, and 20MSR. Complementarily, a higher proportion of athlete Rs was reported in TS-G vs. RS-G for SJ (50% vs. 30.3%, respectively), CMJ, and total kicks (16.6% vs. 0%). In conclusion, the addition to the regular training of a HIIT with specific-techniques and repeated-sprints associated with intervals and similar structure of the combat during 4 weeks of training can improve the concentric characteristics of lower limb performance, although they were not the sufficient stimuli in the other components of TKD-related fitness. Copyright © 2021 Ojeda-Aravena, Herrera-Valenzuela, Valdés-Badilla, Cancino-López, Zapata-Bastias and García-García.